Examining Linkage Leadership Style, Employee Commitment, Work Motivation, Work Climate on Satisfaction and Performance - Megawaty, M.; Hamdat, Aminuddin; Aida, Nur (Manunggal Halim Jaya, 2022)
This study aims: to test and analyze the influence of leadership style, employee commitment, work motivation, and work climate on employee job satisfaction with direct and indirect effects. This study uses primary data from a survey of 221 employees as sample. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results showed that: (1) empirically, the leadership style, employees commitment, work motivation, and work climate had a positive and significant effect on job satisfaction; (2) employees commitment, work motivation, and work climate have a positive and significant effect on employees performance through job satisfaction as an intervening variable, while leadership style has no significant effect; (3) employee commitment, work motivation, and work climate indirectly have a positive and significant effect on employees performance through job satisfaction as an intervening variable, while the leadership style has no significant effect; and (4) job satisfaction has a positive and significant direct influence on employees performance. This study suggested that work motivation, employee commitment, and work climate that provide significant influence need to be maintained, while leadership styles that have insignificant influence on employee performance need to be improved and prioritized as the company's efforts to improve job satisfaction and employee performance.